Prevalence and correlates of psychotropic drug use in Dutch nursing home patients with young‐onset dementia. (29th April 2019) - Mulders, Ans J.M.J.; Zuidema, Sytse U.; Leeuwis, Renée; Bor, Hans; Verhey, Frans R.J.; Koopmans, Raymond T.C.M.
Abstract : Objectives: Neuropsychiatric symptoms (NPSs) in dementia patients in nursing homes are common and often treated with psychotropic drugs. Thus far, studies on psychotropic drug use (PDU) mainly focused on elderly patients with dementia. It is important to know the prevalence and correlates of PDU in patients with young‐onset dementia (YOD) to optimize NPS treatment and reduce excess PDU in this group. Design: The Behavior and Evolution in Young‐Onset Dementia (BEYOnD) study is a cross‐sectional study in 230 residents with YOD in eight nursing homes providing specialized YOD care. PDU was registered from medical charts. The influence of age, gender, severity, and type of dementia, NPS, and agitation on PDU was analyzed. Results: Eighty‐seven percent of the residents used psychotropic drugs, and 47% used two or more psychotropic drugs. No significant associations with age, gender, dementia subtype, and dementia severity were found. Depressive symptoms showed an association with the use of antidepressants, nighttime behavior with use of hypnotics, and verbal agitation with antipsychotics. Apathy was strongly associated with lower PDU. Conclusions: Nursing home patients with YOD have a high prevalence of PDU. The association with NPS raises questions of efficacy of these drugs in managing NPS. Patients with apathy had a lower chance of using psychotropics. More research on indications and effects of psychotropic drugs is needed, as well as on (nonpharmacological) alternatives for managing challenging behavior in YOD.